Journey in time and space - Edgard NEHMÉ (International Arab Journal of Dentistry (IAJD), 2020)
If it is terrifying to think that life can be at the mercy of themultiplication of these infinitely small, it is also comfortingto hope that science will not always remain powerless infront of such enemies.Louis PasteurChemist, founder of medical microbiology